Philosophy revalued in mental healthcare - Raabe, Peter Bruno (Array, 2021)
Since the early 20th century philosophy has been generally considered to be a useless academic pursuit. But most so-called talk therapies in the field of mental healthcare are in fact thinly disguised applied philosophy. This essay argues that teaching the contents of philosophy, and the philosophical discursive skills can be of great benefit to the proficiency of clinicians and other professionals in the mental healthcare field.